Efficient Soluble Expression and Application of SpCas9 Protein - LIAO Qing, ZHENG Junwei, WANG Bin, PAN Li (Shipin Kexue, 2023)
Clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9’s main element Cas9 protein is generally expressed by Escherichia coli, but in the process of expression and purification, Cas9 protein is prone to problems such as the formation of insoluble inclusion bodies, high endotoxin content, incorrect protein folding due to too large protein molecules, and low yield. This study aimed to achieve efficient soluble expression of Streptococcus pyogenes Cas9 (SpCas9) protein in E. coli for the purpose of promoting its application and popularizing gene editing technology. The solubility-enhancing tag GB1 was applied to improve the expression level and solubility of Cas9 protein, and a multiple promoter strategy was used to further improve the expression level of Cas9 protein. As a result, the expression of Cas9 protein was increased by 3.52 times. In vitro enzymatic digestion analysis showed that the functional activity of Cas9 protein was not affected by fusion with GB1. Furthermore, a ribonucleoprotein (RNP) complex was assembled and transformed into the host Aspergillus niger, so that the pyrG gene was successfully destroyed.